OPTIMIZING THE POTENTIAL OF UNISBA RETIREMENTS THROUGH TRAINING IN CALCULATION OF THE COST OF PRODUCTS AND SALES AND MANUFACTURE OF CHEESE PRODUCTS - Yuni Rosdiana; Diamonalisa Sofianty; Elly Halimatusadiah; Riyang Mardini (Kajian Akuntansi, 2023)
One of the sources of concern in retirement is economic problems. Such a problem can be overcome by utilizing available potential and resources, either in terms of education, skills, time, or funds, for productive activities that can make a major contribution to the family economy, one of which is through mentoring cheese production training and product cost calculation. The data used in this research are primary data from the pre-test and post-test results of 48 Unisba pensioners as respondents. Then, the researchers carry out descriptive statistical analysis and inferential analysis of the data results through the average difference test between the pre-test scores and post-test scores, which will later be analyzed. Based on the results of testing by SPSS, there is an increase in post-test results from the results of the previous pre-test with a significance value of <0.05. These results indicate that the training in calculating the cost of production and sales and the manufacture of cheddar cheese has a significant effect in increasing the knowledge of training participants. Keywords: Retirement, Product Cost, Selling Price, Community Service.